2020
DOI: 10.1111/aogs.13786
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the hypertensive disorders of pregnancy in Denmark

Abstract: Abbreviations: BMI, body mass index; IVF, in vitro fertilization; OR, odds ratio; S-25OHD, serum 25-hydroxyvitamin D. AbstractIntroduction: Hypertensive disorders of pregnancy, including gestational hypertension and preeclampsia, are leading causes of morbidity and mortality for both mother and fetus. It has been proposed that vitamin D affects a number of biological processes involved in the pathogenesis of hypertensive disorders of pregnancy.Therefore, a seasonal variation in the risk of these disorders migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Given that an individual will benefit most from supplementation when they are deficient, any potential usefulness of vitamin D in prevention will also be affected by this seasonality: while supplementation may contribute the majority of vitamin D in winter, the same treatment may be dwarfed by the abundance of skin-synthesised vitamin D in the summer, as it has been reported that 30 min of whole skin surface exposure to summer sunshine is equivalent to 10,000–20,000 IU, even in Norway 13 . The impact of season on vitamin D status 14 , 15 and association with disease traits 16 18 is well established and lifestyle factors may strongly affect this 19 or even reverse it 20 . Thus, the supplementation dose, duration and time of year in which a trial is carried out, as well as individual baseline status and other factors, may impact the comparisons of supplemented and placebo arms in trials 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that an individual will benefit most from supplementation when they are deficient, any potential usefulness of vitamin D in prevention will also be affected by this seasonality: while supplementation may contribute the majority of vitamin D in winter, the same treatment may be dwarfed by the abundance of skin-synthesised vitamin D in the summer, as it has been reported that 30 min of whole skin surface exposure to summer sunshine is equivalent to 10,000–20,000 IU, even in Norway 13 . The impact of season on vitamin D status 14 , 15 and association with disease traits 16 18 is well established and lifestyle factors may strongly affect this 19 or even reverse it 20 . Thus, the supplementation dose, duration and time of year in which a trial is carried out, as well as individual baseline status and other factors, may impact the comparisons of supplemented and placebo arms in trials 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In studying the relationship between season of delivery and preeclampsia, summer was chosen as the reference month because most previous studies suggested that the prevalence associated with summer delivery was low (7,(18)(19)(20)(21). Similarly, winter was chosen as the reference season in the analysis of conception season (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies assessed the relationship between conception season or month and HDP. Four studies supported that conception in summer increased the risk of developing HDP (22,(24)(25)(26).…”
Section: Season Of Conception and Hdpmentioning
confidence: 98%
See 2 more Smart Citations